Music of the Gold Coast - Gbeho, Philip (International Library of African Music, 1954)
What do we mean by the term “music” in Africa? It is the combination of three things that are interdependent and never separated: dancing, singing and drumming. The songs are generally short and would probably be dull if it was not for the African’s natural gift of improvisation—which is the very heart of music. Having to repeat the short songs over and over again, we have varied the tune with every repetition, improvising and adding extra notes and tones to keep up the listener’s—and singer’s—interest without totally departing from the particular harmony of the tune. This natural gift of improvisation, thought to be important by great musicians like Bach, is the sign of a man’s true musicianship.
Keywords: Ethnomusicology; Improvisation (Music); Music; Drum; Dance; Africa; Polyrhythm; Performance; Singing; Musical instruments; Drum music; History; Criticism; African Music; Drum (Instrument)